Awareness and use of self-archiving options among academic librarians in Nigerian universities. Issue 1 (4th February 2019) - Okeji, Clement Chukwuma; Eze, Monica Eberechukwu; Chibueze, Nneka Maureen
Abstract : Purpose: The purpose of this study was to investigate the extent to which academic librarians in Nigerian universities use self-archiving options to make their research papers visible globally. Design/methodology/approach: An online survey was designed using SurveyMonkey software to collect data from 394 academic librarians in Nigerian Universities. Findings: The study revealed that the academic librarians in Nigerian universities know and actually use self-archiving options such as ResearchGate, institutional repository and Academia.edu to self-archive their publications. While other promotional tools such as kudos, Mendeley.com and personal websites/servers are not popularly used by the academic librarians. Increased exposure of previously published work, broadens the dissemination of academic research generally, and increases institutions' visibility were among the factors the academic librarians indicated as very important that motivate them to contribute their scholarly output to self-archiving options. Research limitations/implications: One major challenge to the study is that many academic librarians in Nigeria do not check their e-mails regularly to enable them to respond to a request to participate in an online survey; some of them do not have stable internet facilities, whereas others are reluctant to respond to an online questionnaire. These reasons led to a low response rate which makes it difficult to generalize findings. Practical implications: Findings from the study will create awareness for academic librarians in developing countries to see the need to self-archive their pre-print and accepted version of their papers in different self-archiving platforms. Originality/value: Self-archiving of papers by authors will lead to an increased visibility of the author and possible citation of the work and chances of collaboration with international colleagues for research projects.